Synthesis of Hydrophilic Polyelectrolyte as Draw Solute for Forward Osmosis Process - Khongnakorn, W.; Bootluck, W. (Journal of Applied Membrane Science & Technology, 2017)
Synthesis and characterization of hydrophilic polyelectrolyte was performed in this work and used as draw solute for forward osmosis (FO) process. The effect of different ratios of acrylic acid (AA) and benzoyl peroxide (B) on the properties of polyelectrolyte was studied in this work. The physical and chemical properties of draw solution (DS) such as pH, conductivity, osmolality, viscosity, molecular weights and functional group were investigated. Results showed that the solution osmolality increased with increasing AA/B ratio. Self-synthesized polyelectrolytes with different molecular weights (MWs) were further correlated with its solution osmolality. The self-synthesized polyelectrolytes of PAA-K and PAA-Na showed an increasing of hydrophilic functional groups such as –OH or COOH. PAA-Na with lower MW and high osmotic pressure in the aqueous solution is found to exhibit a lower reverse solute flux during FO process. Meanwhile for the polyelectrolyte with higher MW, higher viscosity and lower diffusion coefficient were reported.